Understanding legitimation and the framing of claims: challenging housing demolitions, fighting for a home in Lenasia - Molopi, Moloi Edward (My University, 2015)
In November 2012, the Gauteng Provincial Government engaged on a programme to demolish houses that were illegally built on government land in Lenasia, a suburb located 30 kilometres south of Johannesburg. Over 50 homes were demolished with further demolitions being scheduled. The demolitions spurred various actors into action. Following a court interdict applied for by the South African Human Rights Commission (SAHRC) on behalf of the residents, the government was then forced to cease with the demolitions. Within the dispute various claims have been advanced and legitimation processes entered into. This study uses the case of the demolitions in Lenasia to investigate the nature of legitimation and the framing of claims. This is done through a consideration of the different actors in the demolitions and each of the claims advanced. The central claims of this work are that legitimacy is context-specific and in a state of constant formation. Furthermore, claims are used to express worldviews and they serve as strategic standpoints for access to various goods.
A research report submitted to the Faculty of Engineering and the Built Environment: University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Town and Regional Planning (Urban Studies)
Keywords: Housing development; South Africa, Johannesburg; Lenasia; Social conditions